Optimalisasi Pengelolahan Jaringan Dengan Pembatasan Bandwidth dan Blokir Akses Tertentu Pada PT Laxo Global Akses Dengan Menerapkan Metode NDLC - Adiffanani Ramdansyah; Hamzah Setiawan; Uce Indahyanti; Ade Eviyanti (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This research focuses on optimizing network management at PT Laxo Global Akses by implementing bandwidth restrictions and restricting access to non-work related websites and applications. Internet usage in the company was previously unrestricted, resulting in decreased productivity and unstable network performance, especially during peak hours. To address these issues, this research applies the Network Development Life Cycle (NDLC) methodology and utilizes MikroTik devices for configuration. Key features such as Queue Tree for bandwidth distribution, Firewall Filtering for access control, and Hotspot User Management for user authentication were implemented. The redesigned network topology allows for more structured traffic management and real-time monitoring. The test results show that all test scenarios have succeeded as expected, so it can be concluded that the network configuration and policies implemented in the NDLC process were 100% successful at the implementation and testing stages.